Childhood poverty and malnutrition in the Department of Huánuco during the COVID-19 pandemic - Tiburcio Rosas, Luis Geyner (2025)
Objective: This study purpose to examine the relationship between poverty and malnutrition in infants under 5 years of age in the Department of Huánuco during the COVID-19 pandemic period (2020–2022). Materials and methods: The research it is developed under a approach quantitative of type basic, with a non-experimental design and applying the technique of document analysis. Data were obtained from the Peruvian Information System on the Nutritional Status of Children and Pregnant Women and the National Institute of Statistics and Informatics (INEI). Results: The findings indicate that between the years 2020 and 2022, there was an evidenced average increase of 0.36 percentage points in child malnutrition indicators and 1.45 percentage points in the indicators of poverty levels, which reflects a tendency slight but consistent deterioration in these conditions in the department analyzed. Conclusions: It is concluded that the COVID-19 pandemic disrupted the progress made in previous years in reducing poverty and malnutrition, intensifying the condition of vulnerability of the affected child population.